A transgenic zebrafish for in vivo visualization of cilia - Zhang, Hongyu (2023)
Cilia are organelles for cellular signalling and motility. Mutations affecting ciliary function are also associated with cilia-related disorders (ciliopathies). The identification of cilia markers is critical for studying their function at the cellular level. Due to the lack of a conserved, short ciliary localization motif, the full-length ARL13b or 5HT6 proteins are normally used for cilia labelling. Overexpression of these genes, however, can affect the function of cilia, leading to artefacts in cilia studies. Here, we show that Nephrocystin-3 (Nphp3) is highly conserved among vertebrates and demonstrate that the N-terminal truncated peptide of zebrafish Nphp3 can be used as a gratuitous cilia-specific marker. To visualize the dynamics of cilia in vivo, we generated a stable transgenic zebrafish Tg (β-actin: nphp3N-mCherry)sx1001. The cilia in multiple cell types are efficiently labelled by the encoded fusion protein from embryonic stages to adulthood, without any developmental and physiological defects. We show that the line allows live imaging of ciliary dynamics and trafficking of cilia proteins, such as Kif7 and Smo, key regulators of the Hedgehog signalling pathway. Thus, we have generated an effective new tool for in vivo cilia studies that will help shed further light on the roles of these important organelles.